Gambaran Aktivitas Fisik Remaja Selama Pembelajaran Daring di SMK Kesehatan Citra Medika Sukoharjo - Aguwitha Regshal Mrewassari; Anjar Nurrohmah (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2022)
Physical activity is a body movement produced by muscles that requires energy expenditure, including activities performed while playing, working, engaging in recreational activities, and doing household chores. Adolescence is a period of self-transition from children to adults in the age range of 10-19 years and is a period of growth and development that is quite meaningful physically, biologically, psychologically, and intellectually. The change in the learning system to online during the pandemic caused a decrease in activity. Objective: To identify the characteristics of physical activity and the level of physical activity of adolescents during online learning at Citra Medika Health Vocational School Sukoharjo. This type of research is descriptive retrospective with a cross sectional design. The population in this study were all students of class X and XI SMK Kesehatan Citra Medika Sukoharjo. Data collection techniques using the Physical Activity Questioner-Addolenst (PAQ-A) questionnaire. sample selection using Stratified Random Sampling technique. The results of the level of physical activity of adolescents during online learning at Citra Medika Health Vocational School Sukoharjo had a light physical activity level of 176 students (93.1%) and a moderate activity level of 13 students (6.9%). Based on the results of the study, it was shown that the level of physical activity of adolescents during online learning was light.